Fluorescent properties anionic derivative of thioflavin T - Maskevich, Alexander A. (Journal of the Belarusian State University. Physics, 2021)
We have investigated the spectral properties of a new benzothiazole dye – a thioflavin T derivative – 3-sulfopropyl-5-methoxy-2-[3-(3,5-diethyl-2-benzothiazolidene)-1-propienyl]-benzothiazolium (Th-C11). Based on quantum-chemical calculations, it is shown that the molecule in the ground state has a flat structure. In an excited state, the minimum energy corresponds to a twisted conformation, in which the aromatic fragments are arranged orthogonally. Since the twisted state is non-fluorescent, the transition to this state (torsion relaxation) is a quenching process. Th-C11 dye exhibits the properties of a fluorescent molecular rotor. As a result of experimental studies, it was found that torsion relaxation of molecular fragments is the main process that determines the strong dependence of the quantum yield and the duration of fluorescence decay on the viscosity of the solvent. A characteristic feature of this dye is the sensitivity of the fluorescence parameters – the quantum yield, the decay duration and the position of the spectrum not only to the viscosity, but also to the polarity of the medium. The paper also explains the dependence of the position of the absorption and fluorescence spectra on the polarity and viscosity of the solvent as a result of the manifestation of the processes of torsion and solvation relaxation of the chromophore and solvent molecules.
Keywords: derivatives of thioflavin T; quantum-chemical calculations; fluorescent molecular rotor; amyloid fibrils